Nurturing Patriotism Among Participants of SB AMI Al Rahmah - Arief Hidayat; Fanani Firdaus; Sidiq Diwa Montella; Flora Ramona Sigit Prakoeswa; Erma Widyastuti; Bayu Hendro Wicaksono (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
This research aims to explore efforts to instill a spirit of nationalism and motivation to learn in students at the AMI Al Rahmah Penang Guidance Studio. The research method used is qualitative, with data collection techniques through observation, interviews and documentation. This observation involves observing students' activities in singing regional national songs, understanding the role of national heroes, and learning traditional regional dances. This step was taken as an approach to root a sense of love for the country in Sanggar Guidance students. Apart from that, learning methods are also implemented through grouping students based on their abilities and interests. From the research results, it was revealed that the introduction and application of national songs has the potential to help instill a sense of nationalism in students. Apart from that, dividing study groups also helps students understand the material better, improves cooperation, and stimulates their learning motivation.